Bouveretov sindrom - visoki biliarni ileus - Košorok, Pavle (Medicinski razgledi, 1996)
The article presents a female patient that was operated in acute state for gallstone ileus without a prior anamnesis having been taken. Due to multiple stones, the ileus recurred with unclear starting symptoms lasting for several days, which, in retrospect, were defined as Bouveret's syndrome. Eight days after the operation clear symptoms of gallstone ileus developed and it was operated again. A third calculus passed spontaneously, also with temporary symptoms of Bouveret's syndrome. The hypothesis put forward is that Bouveret'ssyndrome is rather frequent in clinical practice though it is diagnosed more rarely because most patients seek help in the state of developed gallstone ileus when the symptoms of Bouveret's syndrome have already passed. If, in view of modern diagnostic methods, Bouveret's syndrome were diagnosed in time, conservative treatment would be possible as well, especially in high-risk patients.
Keywords: prebavila; črevesje; kirurgija